The Relationship between Healthy Lifestyle and Physical Fitness in Extracurricular Sports Students - Muhammad Ahsan Asy-Syamail; Muh. Isna Nurdin Wibisana; Osa Maliki (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. The objectives of the study are to investigate the elements that impact the adoption of healthy lifestyle habits and levels of physical fitness among extracurricular students at SMP 6 Hassanudin Semarang. The research is focused on establishing the connection between healthy lifestyle habits and the level of physical fitness among students participating in extracurricular sports at SMP 6 Hassanudin Semarang. Materials and Methods. The research methodology used in this study is correlational and quantitative in nature. The study's population comprised all extracurricular members of SMP 6 Hassanudin Semarang, totaling 30 students. Total sampling was used as the sampling technique, which means the entire population was included in the sample. A questionnaire was used for the assessment of a healthy lifestyle, while the Indonesian Physical Fitness Level exam (TKJI) was used for the evaluation of physical fitness. The analysis methods employed included descriptive analysis, precondition tests, and hypothesis testing. Results. The scores for healthy lifestyle were as follows: 5 students scored very well, 17 students scored well, 6 students scored moderately, and 2 students scored poorly. In terms of physical fitness level, 7 students were classified as having a good level of fitness, 19 students as having a moderate level of fitness, and 4 students as having a poor level of fitness. The correlation coefficient (r) from the analysis is 0.649, which is higher than the critical value (r table) of 0.361, indicating a significant relationship between a healthy living pattern and the level of physical fitness. Conclusion. The results of the study show a notable connection between maintaining a healthy way of life and the level of fitness among extracurricular students at Hasanudin 6 Middle School in Semarang. Students who lead an unhealthy lifestyle should integrate regular physical exercise and other activities into their daily schedule.